Evaluasi Kinerja Bagan Kendali Fm Pada Proses Short-Run - Darmanto, Darmanto (Performa: Media Ilmiah Teknik Industri, 2018)
The manufacturing production process that is currently trend is short-run. Short-run process is a job shop and a just in-time. These causes the process parameters to be unknown due to unavailability of data and generally a small amount of product. The control chart is one of the control charts which  designed for the short run. The procedure of the control chart follows the concept of succesive difference and under the assumption of the multivariate Normal distribution. The sensitivity level of a control chart is evaluated based on the average run length (ARL) value. In this study, the ARL value was calculated based on the shift simulation of the average vector by recording the first m-point out of the control limits. The average vector shift simulation of the target () is performed simultaneously with the properties of a positive shift (=+ δ). Variations of data size and many variables in this study were m = 20, 50 and p = 2, 4, 8, respectively. Each scheme (a combination of δ, m and p) is iterated 250,000 times. The simulation results show that for all schemes when both parameters are known ARL0 ≈ 370. But, when parameters are unknown, ARL1 turn to smaller. This conclusion also implied when the number of p and n are increased, it reduce the sensitivity of the control chart.